Synchronization of the 2025 Criminal Prosedur Code Draft With the National Criminal Code: A Review of Obstacles, Gaps, and the Ultimum Remedium Principle - Purba, Tumian Lian Daya; Palit , Silvester Magnus Loogman (Jurnal Hukum dan Keadilan, 2025)
The enactment of the 2022 Criminal Code (KUHP) marks a milestone in reforming Indonesia’s national law, replacing the Dutch colonial legacy that has prevailed for over a century. Nevertheless, its effectiveness depends on the existence of procedural law as an implementing instrument, namely the 2025 Draft Criminal Procedure Code (RKUHAP), which is currently under discussion. Synchronization between the KUHP and the RKUHAP is essential since substantive and procedural law form a unified criminal law system. This study aims to analyze the synchronization of the 2025 RKUHAP with the KUHP, focusing on obstacles, normative inconsistencies, and the application of the principle of ultimum remedium. The method employed is normative juridical legal research with legislative, conceptual, and comparative approaches, complemented by case analysis. Research data consist of primary legal materials (KUHP, RKUHAP, and related regulations), secondary materials from academic literature, and tertiary supporting materials. The analysis is conducted qualitatively by identifying and interpreting norms, then testing them against doctrines and criminal law principles. Findings reveal three issues: obstacles from overlapping articles and different orientations, with RKUHAP remaining retributive while KUHP embraces restorative justice; normative inconsistencies in detention provisions that risk violating legality and fair trial principles; and inadequate reflection of ultimum remedium since minor and administrative offenses still tend toward criminalization. The study concludes that without proper synchronization, risks of legal disharmony and excessive criminalization may emerge, undermining human rights protection. Therefore, ultimum remedium must serve as the guiding principle in drafting the 2025 RKUHAP to ensure a fair, modern, and rights-oriented criminal law system in Indonesia.